Inactivation of Membrane Surface Ecto-5'-nucleotidase by Sodium Nitroprusside in C6 Glioma Cells - Tadanori Kumasaka; Isao Matsuoka; Hirobumi Mashiko; Shin-ichi Niwa; Junko Kimura (Elsevier, 2011)
Abstract.: Ecto-5'-nucleotidase (NT5E), a predominant enzyme that produces extracellular adenosine from AMP, plays an important role in a variety of physiological and pathophysiological processes. This study was performed to identify agents that affect NT5E activity using C6 glioma cells. When cells were incubated with sodium nitroprusside (SNP), phorbol 12-myristate 13- acetate, forskolin, lipopolysaccharide, or interferon-γ, only SNP inhibited NT5E activity in a time- and concentration-dependent manner (IC50 = 1.2 μM). The inhibitory effect of SNP was long-lasting even after SNP washout; and its action was not mimicked by nitric oxide generating agents, 8-bromo cyclic GMP, ferricyanide, ferrocyanide, or sodium cyanide. SNP did not change NT5E mRNA level or membrane surface protein expression. Similar to SNP, Fe2+ inhibited NT5E activity, but to a lesser extent. Although Fe2+ is known to increase oxidative stress, Fe2+-mediated oxidative stress was not involved in SNP inhibition of NT5E because the inhibition of NT5E by SNP was not affected by superoxide dismutase and catalase. In contrast, addition of Zn2+, an essential metal co-factor of NT5E activity, prevented SNP from inhibiting NT5E. These results suggest that SNP disrupts a critical Zn2+-dependent enzyme activity and might be useful as a pharmacological tool for inhibiting NT5E. Keywords:: ecto-5'-nucleotidase, sodium nitroprusside, Zn2+, Fe2+, C6 glioma cell